p19INK4d is involved in the cellular senescence mechanism contributing to heterochromatin formation - Sonzogni, Silvina Veronica (2014)
Background: During evolution, organisms with renewable tissues have developed mechanisms to prevent tumorigenesis, including cellular senescence and apoptosis. Cellular senescence is characterized by a permanent cell cycle arrest triggered by both endogenous stress and exogenous stress. The p19INK4d, a member of the family of cyclin-dependent kinase inhibitors (INK4), plays an important role on cell cycle regulation and in the cellular DNA damage response. We hypothesize that p19INK4d is a potential factor involved in the onset and/or maintenance of the senescent state. Methods: Senescence was confirmed by measuring the cell cycle arrest and the senescence-associated β-galactosidase activity. Changes in p19INK4d expression and localization during senescence were determined by Western blot and immunofluorescence assays. Chromatin condensation was measured by microccocal nuclease digestion and histone salt extraction. Results: The data presented here show for the first time that p19INK4d expression is up-regulated by different types of senescence. Changes in senescence-associated hallmarks were driven by modulation of p19 expression indicating a direct link between p19INK4d induction and the establishment of cellular senescence. Following a senescence stimulus, p19INK4d translocates to the nucleus and tightly associates with chromatin. Moreover, reduced levels of p19INK4d impair senescence-related global genomic heterochromatinization. Analysis of p19INK4d mRNA and protein levels in tissues from differently aged mice revealed an up-regulation of p19INK4d that correlates with age. Conclusion: We propose that p19INK4d participates in the cellular mechanisms that trigger senescence by contributing to chromatin compaction. General significance: This study provides novel insights into the dynamics process of cellular senescence, a central tumor suppressive mechanism.